THE INFLUENCE OF EDUCATIONAL ATTAINMENT, JOB TRAINING, AND INFORMATION TECHNOLOGY SOPHISTICATION ON THE EFFECTIVENESS OF ACCOUNTING INFORMATION SYSTEMS IN SAVINGS AND LOAN COOPERATIVES - Ni Nengah Budi Artini; I Made Pande Dwiana Putra (Adisam Publisher, 2025)
The effectiveness of accounting information systems (AIS) is key to promoting transparency and accountability in cooperative financial reporting. However, many cooperatives in Denpasar have yet to optimize the use of AIS. This study aims to examine the influence of educational attainment, job training, and information technology sophistication on AIS effectiveness in savings and loan cooperatives (SLCs) in Denpasar City. Employing a quantitative approach with a survey method, this study collected data from 112 respondents representing 56 active cooperatives selected via purposive sampling. Data were gathered using questionnaires and analyzed using multiple linear regression in SPSS. The results reveal that educational attainment, job training, and information technology sophistication each have a positive and significant effect on AIS effectiveness.